Foot Posture Characteristics in Medial Knee Osteoarthritis Patients - Leni Kopen; Angela BM. Tulaar; Nyoman Murdana (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Alteration of foot posture may influence the knee loading, particularly in medial compartment. The purpose of this study was to find the relation of foot postures with clinical finding in medial knee osteoarthritis (KOA).Methods: Subjects with medial KOA who met inclusion criteria were recruited consecutively, in Nursing home on August to October 2018. The foot posture has determined by Foot Posture Index (FPI). The severity of KOA has measured by Kelgreen-Lawrence (KL) grading system, and pain level using numeric rating score (NRS).Results: There were 37 subjects consisted of male and female with normal foot subsequently 17(8.5%) and 3(15%), male and female with abnormal food subsequently 3(15%) and 1(16%). There were 12 (32.43%) of pronated foot, 5 (13.51%) of supinated foot, and 20 (54.06%) of normal foot subjects. The subjects with abnormal foot posture have severe medial KOA (p<0.001), while the pain sensation similar between groups (p=0.321, p=0.688).Conclusion: There was a correlation between foot posture and the severity of medial KOA.Keywords: Foot posture, Knee osteoarthritis, Foot posture index, Numeric rating score